Association of ear plug practice and hearing loss among exposed group to noise in auto parts manufacturing industry / Farah Hazwani Mohammed Zaini - Mohammed Zaini, Farah Hazwani (2012)
Introduction: A personal hearing protection device is any device designated to reduce the level of sound reaching the eardrum. Ideally, the most effective way to prevent NIHL is to remove the hazardous noise. Hearing protectors should be used when engineering controls and work practices are not feasible for reducing noise exposure to safe levels. So, a cross sectional study was carried out among auto parts manufacturing industry workers in Rawang, Selangor. The objective of this study was to study the association of ear plug usage to hearing loss among noise exposed workers at auto parts manufacturing industry. Methodology: Sixty workers (n=60) were involved in this study after considered the inclusive criteria and exclusive criteria. Questionnaires were used to obtain sociodemography data and observation methods were used to identify the ear plug usage from respondents. Noise Dosimeter (EOGE 4 Quest Tech) was used to measured the personal noise exposure and ANSI S1 .4 Type 2 sound level meter was used to measure workplace noise level. All studied samples were subjected to complete Audiometric Test using pure tone Audiometer (Silent Cabin Model 'S'). The